2011
DOI: 10.1111/j.1538-7836.2011.04203.x
|View full text |Cite
|
Sign up to set email alerts
|

Hindered dissolution of fibrin formed under mechanical stress

Abstract: BackgroundRecent data indicate that stretching forces cause a dramatic decrease in clot volume accompanied by gross conformational changes of fibrin structure.ObjectiveThe present study attempts to characterize the lytic susceptibility of fibrin exposed to mechanical stress as a model for fibrin structures observed in vivo.Methods and resultsThe relevance of stretched fibrin models was substantiated by scanning electron microscopic (SEM) evaluation of human thrombi removed during surgery, where surface fibrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 28 publications
4
112
0
1
Order By: Relevance
“…This results in lower penetration of tPA, limiting its fibrinolytic action within the thrombus. 7,22,23 Previous semiquantitative histological analyses of thrombi obtained by thromboaspiration from the coronary artery have shown that the fibrin content of the thrombus increases over several hours in patients with ST-segmentelevation myocardial infarction. The time-dependent changes in the thrombus may affect the efficacy of thrombolytic treatment, as observed in our results.…”
Section: Discussionmentioning
confidence: 99%
“…This results in lower penetration of tPA, limiting its fibrinolytic action within the thrombus. 7,22,23 Previous semiquantitative histological analyses of thrombi obtained by thromboaspiration from the coronary artery have shown that the fibrin content of the thrombus increases over several hours in patients with ST-segmentelevation myocardial infarction. The time-dependent changes in the thrombus may affect the efficacy of thrombolytic treatment, as observed in our results.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters Scanning electron microscope (SEM) imaging of fibrin-Fibrinogen (5.9 M in 25 mM Naphosphate pH 7.4 buffer containing 75 mM NaCl) was clotted for 1 h at 37 °C with 5 or 100 nM thrombin in Eppendorf tubes (pre-treated with 25 v/v% Triton X-100 solution for 1 h and thoroughly washed with water). Clots were fixed, dehydrated, sputter coated with gold and examined as described in (15). Preparation of patterned fibrinogen substrate surface with micro-contact printing and monitoring of plasmin distribution with AFM-Fibrinogen was printed on mica using microcontact printing (25,26).…”
Section: Fdp a Efdp K E Fdp mentioning
confidence: 99%
“…Thus, any model that is based on diffusion, binding and reaction rate parameters gained in homogeneous dilute solutions is necessarily just an approximation of the real situation in fibrin, where an additional level of complexity is rendered by the variability of fibrin meshwork structure (e.g. in cell-free areas of in vivo human thrombi the fiber diameter varies in the range 100 -200 nm and the pore diameter in the range 160 -380 nm) (15). The third type of kinetic models of interfacial proteolysis in fibrin overcomes the limitations related to the deviation from the homogeneity assumptions by introducing a microscale stochastic approach, which operates with single enzyme molecules rather than enzyme concentrations in deterministic equations (16).…”
Section: Introductionmentioning
confidence: 99%
“…30 This has downstream implications in terms of thrombus stability and susceptibility to lysis 29,31 and can influence penetration of cells into thrombi. Models incorporating physiological flow rates have helped define the processes governing thrombus formation.…”
Section: Introductionmentioning
confidence: 99%